KNOWLEDGE, AWARENESS, AND PREVALENCE OF BATHMOPHOBIA AMONG UNDERGRADUATE DENTAL STUDENTS- A QUESTIONNAIRE SURVEY - Sukanth R, Dhanraj Ganapathy, L. Keerthi Sasanka (Drugs and Cell Therapies in Hematology, 2022)
Introduction: Fear or phobia affects each and everyone in some or another way and some people don't lead their life peacefully due to their fear over something . There are many types of phobias that both humans and animals undergo, one such phobia is Bathmophobia, the fear over steep stairs and slopes, this fear of steps is common and mostly affects young children . Aim: The aim of the study is to know the prevalence of bathmophobia among undergraduate dental students in a private institution. Materials and method: A private dental institution was chosen and UG students were asked to answer an online questionnaire containing ten questions, which was already prepared and approved by the guide for the study. The results collected from the questionnaire were then coded in Microsoft Excel and then the coded results were uploaded to SPSS software version 23, for the Pearson chi-square test for descriptive analysis and further depicting it in the form of graphs and pie charts. Results: Bathmophobia was common among the students but there were no severe problems faced by the students due to their fear over steps and slopes. The students felt a little anxious on seeing steep steps and slopes but their fear was controllable and they could easily overcome the fear. Conclusion: prevalence of Bathmophobia among dental students but the fear is controllable and did not cause any serious problems to the students. And this study gave an awareness over the bathmophobia with undergraduate students.